2016
DOI: 10.1186/s13071-016-1349-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination and transmission of Ascaris suum in Danish organic pig farms

Abstract: BackgroundAlthough Ascaris suum is the most common pig nematode, the on-farm transmission dynamics are not well described.MethodsWe performed a 1-year field study on five organic pig farms, mapping egg contamination levels in pens and pasture soil as well as faecal egg counts in starter pigs, finisher pigs, dry and lactating sows. The uppermost bedding material was sampled from three pen areas (resting, intermediate and latrine) of shallow and deep litter pens.ResultsAscaris suum was found on all farms. Averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 35 publications
3
55
2
Order By: Relevance
“…In addition, the lack of an effective control system would require more information on the epidemiological pattern, the availability of the new anthelmintics and the better education of the producers (TAMBOURA et al, 2006). Comparatively, Katakam et al (2016) found the occurrence of A. suum was 15% for lactating sows, a lower value than that obtained by Nissen et al (2011) with growing pigs (39.6% for A. suum). It is possible that the greater A. suum prevalence observed compared the results of other surveys can be explained by the fact that the sows are housed in pens with entirely concrete floors, and thus they were in direct contact with faeces.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the lack of an effective control system would require more information on the epidemiological pattern, the availability of the new anthelmintics and the better education of the producers (TAMBOURA et al, 2006). Comparatively, Katakam et al (2016) found the occurrence of A. suum was 15% for lactating sows, a lower value than that obtained by Nissen et al (2011) with growing pigs (39.6% for A. suum). It is possible that the greater A. suum prevalence observed compared the results of other surveys can be explained by the fact that the sows are housed in pens with entirely concrete floors, and thus they were in direct contact with faeces.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore pigs in such farms are more heavily affected by A. suum infestation. "Organic" farms decrease the level of environmental contamination with A. suum eggs by regular mechanical cleaning of the pigs' living area from feces with further compulsory composting (Katakam et al, 2016). in their experiments studied the relationship between viability of A. suum eggs in deep litter and the litter's humidity and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, these factors include parasitic diseases, such as ascariasis, trichocephalosis, oesophagostomiasis, strongyloidiasis, echinococcosis, cysticercosis, sarcoptosis, balantidiasis and others. The most widespread disease of pigs globally is ascariasis (De Velásquez et al, 2004;Feshenko, 2008;Evstafieva, 2010;Katakam et al, 2016). It causes great damage to swine-rearing.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these the nodule worm Oesophagostomum induces only a weak reaction of the host’s immune system [1], making the latter unsuitable for immunological intervention. With regard to the economic importance, porcine nematodes, especially Strongyloides , Trichuris and the nodule worms, have decreased in prevalence sind the advent of broad-spectrum anthelminthics and modern management, although A. suum prevalences can still be considerable, especially in traditional management systems or on organic farms [16, 29–31]. …”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%